Traditional ethnomedicinal practices for gynecological disorders among the Gond tribe of Chhattisgarh: a regional perspective - Kolla, Andrea; Gawri, Shobha; Kolla, Varaprasad; Sahu, Bharti (International Journal Of Community Medicine And Public Health, 2025)
The Gond tribe, one of the largest tribal communities in India, is predominantly concentrated in Chhattisgarh, particularly in forest villages. Known for their rich cultural heritage and deep connection to nature, the Gonds rely heavily on the forests for their livelihood, including food, medicine, and materials for daily use. Traditional knowledge plays a crucial role in their healthcare, especially in addressing women’s health issues. The Gond community has preserved its ancient practices of folk medicine, using a variety of medicinal plants to treat gynecological disorders such as menstrual irregularities, reproductive health concerns, and postpartum issues. This study focuses on the ethno-medicinal plants used by the Gond tribe for women’s health in regions like Bilaspur, Gariyaband, Korba, and Saraipali. Through field surveys and interviews with local healers and community members, information was gathered on 34 plant species traditionally used for gynecological problems. Detailed data was compiled, including botanical names, plant families, local names, parts used, and medicinal properties. The Gonds utilize a diverse range of plants, preparing specific remedies for different gynecological issues, including menstrual disorders, fertility challenges, and menopause symptoms. Despite the availability of modern healthcare, these traditional remedies continue to be highly valued for their effectiveness. The findings of this study emphasize the importance of preserving indigenous knowledge and the need for conserving these valuable plant resources. It advocates for integrating traditional medicine with modern healthcare systems to improve women’s health outcomes in the region and ensure the sustainability of this ethno-botanical knowledge.